Ability to write literary news based on interview text using questionnaire method for class x students of Ar-Raudhatul Hasanah Islamic Boarding School - Aminah, Siti; Kartolo, Rahmat (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
A Writing feature news based on interview text using the questionnaire method is one aspect of learning Indonesian in class X MAS.sFemale students are expected to be able to write feature news based on good and correct interview texts. This research aims to describe the ability to write feature news based on interview text using the questionnaire method. The population of this study were all class X MAS students at the Ar-Radhatul Hasanah Islamic boarding school in Medan, totaling 191 female students. The sample for this research was taken from 25% of the total population, namely forty-six female students who were randomly distributed in each local class X. The method used in this research was the descriptive method. This method is used in accordance with the problem and research objectives which are to describe the ability to write feature news based on interview text using a questionnaire method for class X MAS students at the Ar-Raudhatul Hasanah Islamic boarding school in Medan. Judging from the percentage distribution of scores, of the forty-six female students/students who were sampled, it was found that 34 (74%) female students were in the 80-100 range, including the very good category, and 12 (26%) female students were in the 70-79 range. included in the good category